Proposed upgrading of main building Pangkor Village Beach Resort, Pantai Pasir Bogak, 32300 Pulau Pangkor, Perak Darul Ridzuan / Noor Lizia Shihabuldin - Shihabuldin, Noor Lizia (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the student of Diploma in Interior Architecture is a manisfestation towards the student’s knowledge about the world aspect on interior design that had been learn from basic to the final presentation on the proposed design. The project have been chosen for the final project is upgrading of Pangkor Village Beach Resort at Pulau Pasir Bogak 32300, Pulau Pangkor, Perak Darul Ridzuan. The proposed of upgrading this project is to attract tourist from local and international . At the same time to promoted the tourism industries in our country especially in Pangkor Island. Besides, the target for upgrading this project is to upgrade the image and identity of the resort in order to show the attractiveness of the resort in Pangkor island. Its also to arrange the flow system in the interior of the building. Student should also be focused on the characteristics of the environment, customer requirements and existing space before selecting the appropriate concepts and images for this project. At the same time it can attract the attention of visitors through the concepts and image that will be applied in space. Before start to do work of designing, the students also need to do research work on existing space, such as issues and problems that coincided with objectives of the study.